2004
DOI: 10.1124/dmd.104.001123
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution of Concentrative and Equilibrative Nucleoside Transporters in Male and Female Rats and Mice

Abstract: ABSTRACT:Concentrative nucleoside transporters (Cnts) and equilibrative nucleoside transporters (Ents) have essential physiological functions and are important in disposition of anticancer and antiviral nucleoside analogs. Information on tissue distribution of Cnts and Ents in rodents is sparse. Thus, the present study aimed to determine the distribution of Cnt1-3 and Ent1-3 transcripts in 19 tissues of Sprague-Dawley rats and C57BL/6 mice of both genders. These six transcripts were quantified using the branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 36 publications
7
103
0
2
Order By: Relevance
“…Little 150 kDa FabGAA was detected in liver where the protein existed predominately as the 76 kDa lysosomal form (Fig. 3f), which is consistent with low expression of ENT2 and high expression of M6PR in this tissue [20,30]. At 9 h, the amount of fulllength FabGAA was significantly reduced while the 76 kDa form remained unchanged in heart and skeletal muscles (Fig.…”
Section: Distribution Of Fabgaa In Mouse Tissues Was Heterogeneoussupporting
confidence: 70%
See 1 more Smart Citation
“…Little 150 kDa FabGAA was detected in liver where the protein existed predominately as the 76 kDa lysosomal form (Fig. 3f), which is consistent with low expression of ENT2 and high expression of M6PR in this tissue [20,30]. At 9 h, the amount of fulllength FabGAA was significantly reduced while the 76 kDa form remained unchanged in heart and skeletal muscles (Fig.…”
Section: Distribution Of Fabgaa In Mouse Tissues Was Heterogeneoussupporting
confidence: 70%
“…In addition, a recent study demonstrated that ERT with 3E10Fv-MTM1 fusion protein improved muscle function and pathology in mice with X-linked myotubular myopathy [17]. 3E10 penetrates cells via equilibrative nucleoside transporter 2 (ENT2) [18] that is expressed at high levels in human and rodent skeletal muscles and heart [19,20], making it an ideal vehicle for cytoplasmic delivery of therapeutic GAA in muscle tissues of Pompe disease. A 3E10-GAA fusion should enable ENT2-mediated uptake to clear extra-lysosomal glycogen in muscle fibers while retaining the ability to degrade lysosomal glycogen via M6PR-mediated uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, this study concluded that activation of JNK-cJun pathway negatively regulates mENT1 (Leisewitz et al, 2011). Current knowledge suggest that ENT3 is present in most tissues, including brain (Lu et al, 2004). It was found to co-localize with lysosomal markers and showed broad selectivity and low affinity towards the naturally occurring nucleosides and was unaffected by micromolar NBMPR, dipyridamole or dilazep .…”
Section: Molecular Properties Expression and Mechanism Of Transport mentioning
confidence: 88%
“…Amount of CNT1 mRNA in the brain was less abundant than in epithelia (Lu et al, 2004). In the brain, CNT1 mRNA was detected by in cerebral cortex, hypothalamus, hippocampus, cerebellum and choroid plexus (Lu et al, 2004).…”
Section: Concentrative Nucleoside Transportermentioning
confidence: 91%
See 1 more Smart Citation